All quiet on the western front [videorecording (DVD)] - Thomas, Richard, 1951-; Borgnine, Ernest, 1917-2012; Pleasence, Donald; Neal, Patricia, 1926-2010; Remarque, Erich Maria, 1898-1970 (Artisan Home Entertainment, 2002)
In this realistic depiction of the lives of ordinary German soldiers Paul Baumer and his school chums are encouraged to enlist by their bombastic, slogan-chanting teacher, but they quickly learn that actual war is more gore than glory, as they crawl through mud, huddle in trenches, suffer the ordeal of frenzied hand-to-hand combat and dodge screaming shells during World War I.